1983
DOI: 10.1021/ic00166a011
|View full text |Cite
|
Sign up to set email alerts
|

Stability constants of the copper(II) complexes of peptides and peptide amides containing the .alpha.-aminoisobutyric acid residue

Abstract: The proton and copper(II) association constants are measured for eight peptides and four peptide amides, which contain the -aminoisobutyric acid (Aib) residue. The Aib peptides are slightly stronger bases than the corresponding glycyl peptides with a greater difference in the protonation constants for the carboxylate group (0.5-0.6 log unit) than for the amine functional group (0.0-0.25 log unit). The stepwise formation constants for the copper(II)-Aib" peptide complexes indicate that both inductive and steric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The crystal structure of several peptides containing Aib residues shows that a 3 10 -or a-helical conformation is favoured [5,6]. Potentiometric studies dealing with a series of di-and tripeptides containing Aib revealed that these peptides are slightly stronger bases than the corresponding glycyl peptides [7].We have initiated a systematic study of the coordination chemistry of di-and tripeptides containing the Aib residue, in order to redress the almost complete lack of structurally characterized metal complexes with Aib-containing peptides and with the particular interest to investigate how the inductive and steric properties of a-carbon methyl groups affect the structures of the complexes in the solid state. In the coordination chemistry of Aib-based tripeptides, the X-ray crystal structure of the remarkable copper(III) complex [Cu III (H À2 Aib 3 )] AE 2H 2 O AE 1.5NaClO 4 , containing the trianion of tri-a-amino-isobutyric acid as ligand, had been determined [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of several peptides containing Aib residues shows that a 3 10 -or a-helical conformation is favoured [5,6]. Potentiometric studies dealing with a series of di-and tripeptides containing Aib revealed that these peptides are slightly stronger bases than the corresponding glycyl peptides [7].We have initiated a systematic study of the coordination chemistry of di-and tripeptides containing the Aib residue, in order to redress the almost complete lack of structurally characterized metal complexes with Aib-containing peptides and with the particular interest to investigate how the inductive and steric properties of a-carbon methyl groups affect the structures of the complexes in the solid state. In the coordination chemistry of Aib-based tripeptides, the X-ray crystal structure of the remarkable copper(III) complex [Cu III (H À2 Aib 3 )] AE 2H 2 O AE 1.5NaClO 4 , containing the trianion of tri-a-amino-isobutyric acid as ligand, had been determined [8].…”
mentioning
confidence: 99%
“…The crystal structure of several peptides containing Aib residues shows that a 3 10 -or a-helical conformation is favoured [5,6]. Potentiometric studies dealing with a series of di-and tripeptides containing Aib revealed that these peptides are slightly stronger bases than the corresponding glycyl peptides [7].…”
mentioning
confidence: 99%
“…[7][8][9][10][11]13 Margerum and co-workers have investigated and characterized several Cu(II) and Cu(III) complexes with some peptides with respect to their reactivity, structure and products. [43][44][45][46][47] These studies showed that Cu(III) complexes with tripeptides or tetrapeptides decompose with rapid oxidative degradation of the peptides. In addition, some of the authors 29 suggested Cu(III) as an intermediate in the oxidative degradation and cleavage of DNA in reactions involving Cu II GGHG/H 2 O 2 /ascorbic acid (GGHG = glycylglycylhistidylglycine).…”
Section: Mechanism Of Copper Peptides Oxidation In the Presence Of S(mentioning
confidence: 99%
“…As shown by early studies, the replacement of the hydrogen atoms of the C a carbon of glycine with methyl groups produces severe restrictions on the conformational freedom of the molecule and, consequently, Aib is a strong promoter and stabilizer of folded (b-bends) and 3 10 or a-helical structures [24]. Despite the special properties of Aib, there is a limited number of reports concerning the coordination chemistry of Aib-based small peptides [21][22][23][25][26][27][28][29]; these reports are confined to copper complexes. Our interest in this chemistry is mainly to investigate how the inductive and steric properties of the a-carbon methyl groups affect the structures of the complexes in the solid state and how this may alter the pharmacological properties of the new compounds.…”
Section: Introductionmentioning
confidence: 99%